2012
DOI: 10.1155/2012/741638
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition and Embryotoxicity ofIndigofera suffruticosaon Early Development ofAedes aegypti(Diptera: Culicidae)

Abstract: Aqueous extract of Indigofera suffruticosa leaves obtained by infusion was used to evaluate the oviposition, its effect on development of eggs and larvae, and morphological changes in larvae of Aedes aegypti. The bioassays were carried out with aqueous extract in different concentrations on eggs, larvae, and female mosquitoes, and the morphological changes were observed in midgut of larvae. The extract showed repellent activity on A. aegypti mosquitoes, reducing significantly the egg laying by females with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…In phytochemical studies of I. suffruticosa leaves the Indican was identified, isolated and purified (Vieira, 2011). Recently, protective effects on liver tissue, antitumor activity and embryotoxicity on Aedes aegypti have been tested with extract of I. suffruticosa leaves (Lima, 2012;Vieira et al, 2012). In the present study, we have investigated the liver tissue of mice bearing Sarcoma 180 submitted to subchronic treatment with aqueous extract of Indigofera suffruticosa leaves obtained by infusion and maceration.…”
Section: Introductionmentioning
confidence: 99%
“…In phytochemical studies of I. suffruticosa leaves the Indican was identified, isolated and purified (Vieira, 2011). Recently, protective effects on liver tissue, antitumor activity and embryotoxicity on Aedes aegypti have been tested with extract of I. suffruticosa leaves (Lima, 2012;Vieira et al, 2012). In the present study, we have investigated the liver tissue of mice bearing Sarcoma 180 submitted to subchronic treatment with aqueous extract of Indigofera suffruticosa leaves obtained by infusion and maceration.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological studies showed aqueous extracts of leaves of I. suffuticosa have anti-inflammatory, antimicrobial and embryotoxic properties, besides being used as alternative anticancer and antitumor therapy (12,(15)(16)(17)(18) . The aqueous leaf extract of I. suffruticosa has been shown to inhibit egg hatching, larval ecdyse and to have detergent effects on oviposition of Aedes aegypti mosquitoes (19) . Mice carrying sarcoma 180 had positive hepatic response to subchronic treatment with methanolic extract of I. suffruticosa leaves (20) .…”
Section: Introductionmentioning
confidence: 99%
“…6 It has also been demonstrated that the aqueous extract of leaves of I. suffruticosa inhibits the development of egg hatching, larval ecdysis and has a deterrent effect on oviposition of Aedes aegypti mosquitoes. 10 Mice with sarcoma 180 presented tumor inhibition with low order of toxicity when treated with the extract at the dose of 50 mg.kg -1 (ip) by infusion (64.53 %) and maceration (62.62 %) Table 2. Effects of AELIs on Allium root growth of Allium cepa (n = 5 onions/concentration or group)…”
Section: Allium Cepa Assaymentioning
confidence: 99%
“…9 The aqueous extract of I. suffruticosa leaves has been shown to inhibit the development of egg hatching, larval ecdysis and the deterrent effect on oviposition of Aedes aegypti mosquitoes. 10 Mice with sarcoma 180 showed liver response after sub-chronic treatment with I. suffruticosa extract. 11 The phytochemical study of three (3) bis-indolic alkaloid fractions; Indigo and Indirubin from I. suffruticosa leaves were identified, isolated and purified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation